2013
DOI: 10.7863/jum.2013.32.2.285
|View full text |Cite
|
Sign up to set email alerts
|

Role of Acoustic Shear Wave Velocity Measurement in Characterization of Breast Lesions

Abstract: Acoustic radiation force impulse imaging has potential to characterize breast lesions, both internally and within the boundary zone, and to reflect changes in stiffness within surrounding glandular and subcutaneous fatty tissues caused by malignant tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 50 publications
4
17
0
3
Order By: Relevance
“…VTIQ ARFI elastography enables the quantitative evaluation of tissues stiffness, resulting in shear wave velocity (waves that return from target tissues) estimation. This modern tool showed the highest diagnostic efficacy in differentiating malignant and benign mammary masses, corroborating with recent reports [3,4,18,19,26,27,28,29] and the only reliable parameter. Cut-off values above 2.57 m/s showed an impressive 95% diagnostic accuracy and 98% AUC, with adequate sensitivity and specificity values.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…VTIQ ARFI elastography enables the quantitative evaluation of tissues stiffness, resulting in shear wave velocity (waves that return from target tissues) estimation. This modern tool showed the highest diagnostic efficacy in differentiating malignant and benign mammary masses, corroborating with recent reports [3,4,18,19,26,27,28,29] and the only reliable parameter. Cut-off values above 2.57 m/s showed an impressive 95% diagnostic accuracy and 98% AUC, with adequate sensitivity and specificity values.…”
Section: Discussionsupporting
confidence: 89%
“…The elastogram characteristics obtained in this study were adequate in the diagnosis of malignancy and similar to those previously described in benign mammary lesions in women [4,16,17,18] and bitches [3], with whitish tones (less rigid) in benign and darker tones (rigid not deformable tissues) in the malignant masses. The greater stiffness observed in malignant tumors is a consequence of the stromal reaction induced by the mammary carcinoma, which is associated with increased levels of collagen [3].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In an vitro study, Krouskop et al [26] found that the elastic modulus of the glandular tissue was significantly higher than that of the fatty tissue. An in vivo study with shear wave elastography by Zhou et al [39] reported that the glandular tissue was stiffer than the fatty tissue in both the malignant and benign groups. Our results demonstrated that the diagnostic performance of the elasticity score was superior to that of the GLR.…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, the maximum velocity found in mammary tumors can indicate tissue malignancy (>20.00cm/s), as observed in humans (Dock et al, 1991) and canines (Feliciano et al, 2012), which corroborates the findings observed in the mammary nodules of the female cats in this report. According to the literature, the changes in tumour blood flow, the presence of turbulent flow, high-impedance pulsatile signal (penetration), increased The qualitative assessment of ARFI elastography assists in the conventional ultrasonographic evaluation of mammary neoplasms and increases the sensitivity of the detection of tissue heterogeneity (Yoon et al, 2013) (Zhou et al, 2013) and canines (malignant: 3.33m/s m/s and benign: 1.28m/s m/s) (Feliciano et al, 2014). The increased stiffness of the malignant lesions in the present case report as well as studies in humans (Zhou et al, 2013) may be explained by the presence of a stromal reaction induced by mammary carcinoma associated with increased amounts of collagen components in tumour tissues.…”
mentioning
confidence: 99%